Taxonomic reassessment of the freshwater mussel genus Unio (Bivalvia: Unionidae) in Russia and Ukraine based on morphological and molecular data - Klishko, Olga; Lopes-Lima, Manuel; Froufe, Elsa; Bogan, Arthur; Vasiliev, Lyudmila; Yanovich, Lyudmila (Zootaxa, 2017)
The taxonomy of species within the genus Unio (Bivalvia: Unionidae: Unioninae) in Russia and Ukraine has been contentious due to the lack of correspondence between three concurrent yet divergent classifications. In order to clarify which classification system best reflects the evolutionary relationships among these taxa, we performed detailed morphological analyses on 720 Ukrainian and Russian specimens, complemented with molecular data (COI) from a selected number of specimens. The morphological character data set shows the existence of only three widespread species with slight eco-morphological variations. Statistical analyses of shell morphometric parameters and molecular analyses based on mtDNA COI gene fragment sequences confirm the existence of the same three species within a single genus, Unio, in Russia and Ukraine, that is U. pictorum, U. tumidus and U. crassus. Results from molecular analyses suggest the existence of an additional subgroup within the U. crassus lineage, U. crassus cf. courtilieri that deserves further research. The present integrated approach confirms the validity of the classification by Zhadin (1952) and rejects the complex classifications of Starobogatov et al. (2004) and Bogatov & Kijashko (2016).